Przeciw substancjalizmowi - Kąkol, Tomasz (Filozofia Nauki, 2010)
In this paper I criticize substantialism by analyzing two well-known puzzles con-cerning identity and change - Tibbles the Cat puzzle and the fission paradox. All the approaches assuming substantialism I know lead to untenable consequences (e.g. bilocation) and I conclude that we should seriously take the possibility of processual or eventistic picture of our material life world.